Structural and genetic analysis of epidermal cell differentiation in Arabidopsis primary roots. - Schneider, K; Wells, B; Dolan, L; Roberts, K (1997)
In a screen designed to identify genes in the specification of epidermal cell fate in Arabidopsis primary roots we have isolated 8 new mutants that fall into 6 complementation groups corresponding to the 'root hairless' genes RHL1, RHL2 and RHL3 and the 'ectopic root hair' genes ERH1, ERH2 and ERH3. The erh2 mutant is allelic to pom1, a conditional root expansion mutant, and reveals a possible link between epidermal root hair initiation and radial cell expansion. Apart from erh1 the mutants also show defects in shoot development, indicating a complex role for the affected genes. Mutant phenotypes in the patterning and shape of leaf trichomes in rhl1, rhl2, rhl3 and erh3 were particularly obvious. The root hairless mutants are only partly responsive to increased ethylene concentrations, while the ectopic root hair mutants are fully responsive to reduced concentrations of ethylene, a permissive regulator of root hair initiation. This result and the analysis of double mutants suggest a complex pathway leading to root hair initiation that requires the RHL and ERH genes for correct differentiation.